Molecular evidence for new foodways in the early colonial Caribbean: organic residue analysis at Isla de Mona, Puerto Rico - Lisa Briggs; Jago Cooper; Oliver E. Craig; Carl Heron; Alexandre Lucquin; María Mercedes Martínez Milantchi; Alice Samson (Archaeological and Anthropological Sciences, 2023)
Ceramic objects account for over 90% of the cultural material recovered from archaeological sites in the Caribbean. However, little research has been conducted on molecular evidence for past food production from these same vessels. Forty ceramic sherds from Isla de Mona have been analysed by GC–MS and GC-C-IRMS in order to address questions surrounding foodways in the Greater Antilles prior to and post European arrival. We evaluate evidence for dietary changes to illuminate aspects of cultural exchange between Indigenous populations and the first generations of Spanish colonists. Here, we show that plant residues are found in a variety of pottery forms, with some evidence for non-ruminant and ruminant fats. The dearth of marine biomarkers is curious given the volume of fish bones found in archaeological contexts on Isla de Mona and may offer evidence for spit-roasting, pit-roasting, or the use of a ‘barbacoa’ to cook fish on the island. The ubiquity of plant residues in a variety of pottery forms may relate to the large-scale cultivation and export of cassava ( Manihot esculenta ) from the island. A Spanish olive jar revealed evidence of wine residues, which may constitute the earliest detection of wine residues in pottery found in the Americas.

Biology and pathophysiology of the new human retrovirus XMRV and its association with human disease - Alice Rusmevichientong; Samson A. Chow (Immunologic Research, 2010)